2021
DOI: 10.1021/acsami.1c18450
|View full text |Cite
|
Sign up to set email alerts
|

Limbic Inducted and Delocalized Effects of Diazole in Carbon Nitride Skeleton for Propelling Photocatalytic Hydrogen Evolution

Abstract: Skeleton modification on carbon nitride (g-C3N4) via organic molecules is a recognized effective strategy to improve photocatalytic performance because it can powerfully improve charge separation in the skeleton plane. Herein, a diazole with a unique conjugated structure is bonded on edge of the g-C3N4 skeleton through a moderate polymerization of urea with 4-aminoantipyrine (4AAP). Meanwhile, the Pt nanoparticles selectively deposit on edge of the g-C3N4-4AAP15 nanosheet. It reveals that the robust limbic ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(9 citation statements)
references
References 52 publications
0
9
0
Order By: Relevance
“…The characteristic absorption peaks at 801 and 2180 cm –1 of f-C 3 N 4 are assigned to the stretching vibration of triazine and CN, respectively . A set of absorption peaks from 1700 to 1200 cm –1 including 1240, 1573, and 1633 cm –1 are derived from the stretching vibrations of CN and C–N of the aromatic heterocyclic units of f-C 3 N 4 . The broad absorption peak from 3000 to 3500 cm –1 stands for the stretching vibrations of surface-absorbed O–H and N–H bonds.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The characteristic absorption peaks at 801 and 2180 cm –1 of f-C 3 N 4 are assigned to the stretching vibration of triazine and CN, respectively . A set of absorption peaks from 1700 to 1200 cm –1 including 1240, 1573, and 1633 cm –1 are derived from the stretching vibrations of CN and C–N of the aromatic heterocyclic units of f-C 3 N 4 . The broad absorption peak from 3000 to 3500 cm –1 stands for the stretching vibrations of surface-absorbed O–H and N–H bonds.…”
Section: Resultsmentioning
confidence: 99%
“…35 A set of absorption peaks from 1700 to 1200 cm −1 including 1240, 1573, and 1633 cm −1 are derived from the stretching vibrations of C�N and C−N of the aromatic heterocyclic units of f-C 3 N 4 . 36 The broad absorption peak from 3000 to 3500 cm −1 stands for the stretching vibrations of surface-absorbed O−H and N−H bonds. After the hydrothermal reaction, the conspicuous absorption peak observed at 580 cm −1 is attributed to the vibration mode of the Fe−O bond, while the absorption peaks of f-C 3 N 4 from 1700 to 1200 cm −1 are not changed, confirming the successful formation of Fe 3 O 4 nanoparticles in f-C 3 N 4 .…”
Section: Characterization Of the Samplesmentioning
confidence: 99%
“…The faster migration of electrons from the m -aminophenol unit to the melem unit prevents the release of new fast non-radiative attenuation channels, thus inhibiting the recombination of photogenerated carriers in CN 30 and boosting the photocatalytic activity. 67…”
Section: Resultsmentioning
confidence: 99%
“…The faster migration of electrons from the m-aminophenol unit to the melem unit prevents the release of new fast non-radiative attenuation channels, thus inhibiting the recombination of photogenerated carriers in CN 30 and boosting the photocatalytic activity. 67 PCR was carried out to probe the photo-switching characteristics and separation/transfer efficiency of photogenerated charges of CN and CN 30 . 68,69 In Fig.…”
Section: Catalysis Science and Technology Papermentioning
confidence: 99%
“…[18][19][20][21] Charge transfer in g-C 3 N 4 exhibits anisotropy owing to its π-conjugation structure, resulting in electron transfer being limited in the nanosheets. [22][23][24] Hence, it is crucially important to improve in-plane charge separation for highly-efficient photocatalytic H 2 production. Many studies in the past have shown that intramolecular doping is an efficacious means to propel separation and migration of the electronhole pairs inside the molecular skeleton.…”
Section: Introductionmentioning
confidence: 99%